Trpinčen otrok v zdravstveni negi - Uranker, Nataša (Obzornik zdravstvene nege, 2000)
All forms of child abuse cause different developmental, physical and psychosocial disorders. Health care workers are often the first to encounter an abused child in practice; it is therefore very important that they recognize abuse and take necessary measures. Because of the variety of causes and forms of abuse, the assessment, treatment and necessary measures require cooperation of different professionals and services from social work, health, police, judiciary, education and nongovernmental organizations.
Keywords: Battered child syndrome; Child; Child abuse; Child abuse, sexual; Child, hospitalized; Munchausen syndrome; Nursing; otroci; trpinčenje; zdravstvena nega